Antibiotic sensitivity profile of multidrug-resistant (MDR) Escherichia coli isolated from dairy cow's milk in Probolinggo, Indonesia - AGUS WIDODO; MIRNI LAMID; MUSTOFA HELMI EFFENDI; ASWIN RAFIF KHAIRULLAH; KATTY HENDRIANA PRISCILIA RIWU; LITA RAKHMA YUSTINASARI; SHENDY CANADYA KURNIAWAN; ARIF NUR MUHAMMAD ANSORI‬; OTTO SAHA MARTUA SILAEN; FIDI NUR AINI EKA PUJI DAMEANTI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Widodo A, Lamid M, Effendi MH, Khairullah AR, Riwu KHP, Yustinasari LR, Kurniawan SC, Ansori ANM, Silaen OSM, Dameanti FNAEP. 2022. Antibiotic sensitivity profile of multidrug-resistant (MDR) Escherichia coli isolated from dairy cow's milk in Probolinggo, Indonesia. Biodiversitas 23: 4971-4976. The presence of resistant bacteria in animal products such as milk can be a new threat because it is directly related to the human food chain. Resistant Escherichia coli has been widely studied and detected in farms in developing countries. The aim of present study was to determine the antibiotic resistance profile of E. coli bacteria from dairy cows taken during the milking process from several dairy farms in Probolinggo district, Indonesia. A total of 150 milk samples were obtained from farms and E. coli was isolated and identified on Eosin methylene blue (EMB) media and biochemical test, such as Triple Sugar Iron Agar (TSIA) and indole test, methyl red test, Voges-Proskauer test, and citrate test (IMViC) were also performed. The antibiotic sensitivity profile was screened using the Kirby-Bauer test and results were interpreted according to the CLSI standard. The results showed that 124/150 (82.67%) E. coli bacteria exhibited highest percentage of antibiotic resistance to tetracycline (13.71%), streptomycin (9.68%), trimethoprim (8.87%), chloramphenicol (0.87%), and aztreonam (1.61%). A total of 9/124 (7.26%) E. coli isolates were detected as multidrug-resistant (MDR) and 1/9 (0.81%) E. coli isolate was suspected as extended spectrum ?-lactamase (ESBL) bacteria which was resistant to aztreonam antibiotic. Thus, the threat of multidrug-resistant (MDR) E. coli can come from milk which can affect public health.